PERAN DINAS PEMUDA OLAHRAGA DAN PARIWISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI KOTA BONTANG - Zainal Arifin (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The purpose of this study is to identify and describe the role of the Youth and Sports Department of Tourism in increasing tourist arrivals in the City of Bontang as well as to identify and describe the inhibiting and supporting factors of the Office of Youth Sports and Tourism in increasing tourist arrivals in the City of Bontang. The focus of this research is the role of the Department of Youth Sports and Tourism in increasing tourist arrivals in the City of Bontang. This study uses a qualitative descriptive method with interview techniques to the Department of Youth Sports and Tourism to find out how the role of the Department of Youth Sports and Tourism in increasing tourist arrivals in the City of Bontang so far; the manager to find out how the role of the Department of tourism in the development of the tourism objects they manage; to the tourism industry players to find out how the socialization and the role of the Tourism Office towards the tourism industry that they manage so that they take part in promoting tourism especially in the City of Bontang. Based on the results of this study it can be concluded that the Department of Youth Sports and Tourism has a role in the development of tourism in the City of Bontang. This can be seen in the data received by researchers, namely tourist arrivals in the City of Bontang have experienced an increase from year to year, but still not evenly distributed. This happens because there are still many managers and tourism industry players who complain that there is still a lack of contribution or assistance from the Tourism Office towards the tourism objects they manage. The results of this study researchers can provide suggestions that the need for equal distribution of contributions from the Department of Youth Sports and Tourism to the management of tourism objects and tourism industry players, and also promotion activities more enhanced in order to further increase tourist arrivals in the City of Bontang.